Mutational analysis of the promoter required for influenza virus virion RNA synthesis. - Li, X (1992)
An in vitro RNA synthesis system was established in which the influenza virus virion (minus-sense) RNA was made from the synthetic plus-sense RNA (cRNA) template by the purified viral polymerase complex. The cRNA promoter was studied by mutational analysis using the in vitro system, and on the basis of these experiments, the first 11 nucleotides of the 3' noncoding sequence were found to contain the minimum promoter required for virion RNA synthesis. The addition of extra nucleotides at the 3' end decreased the promoter activity of the templates, indicating that the viral polymerase does not recognize an internal promoter efficiently. The wild-type and mutated RNA templates were also tested in vivo by using the ribonucleoprotein transfection system. In contrast to the in vitro system, it was found that the majority of mutations at the 3'-terminal sequence significantly decreased or abolished chloramphenicol acetyltransferase (CAT) expression. These results suggest that the cRNA promoter overlaps other essential cis elements required for chloramphenicol acetyltransferase expression in vivo.